IMPLEMENTATION OF MARKER PROTEINS USING STANDARDISED EFFECT - Shruti Jain (Journal of Global Pharma Technology, 2017)
In this paper we have discussed the null hypothesized mean,  standardized effect, true population mean, group sample size,  population S.D., type I error rate (Alpha),  critical value ,and power of different marker proteins (AkT, EGFR, ERK, JNK, MK2, IRS and FKHR) theoretically and validate it with Minitab and Statistica Software. Different plots have been plotted between power and sample size, power and standardized effect, power and type 1 error rate. Later we have plotted a correlation graph for different marker proteins which shows mean, SD, max, min, histogram plot, and scatter plot for each marker protein.